CDP-choline: Effects of the procholine supplement on sensory gating and executive function in healthy volunteers stratified for low, medium and high P50 suppression. (December 2014) - Knott, Verner; Smith, Dylan; de la Salle, Sara; Impey, Danielle; Choueiry, Joelle; Beaudry, Elise; Smith, Meaghan; Saghir, Salman; Ilivitsky, Vadim; Labelle, Alain
Diminished auditory sensory gating and associated neurocognitive deficits in schizophrenia have been linked to altered expression and function of the alpha-7 nicotinic acetycholinergic receptor (α7 nAChR), the targeting of which may have treatment potential. Choline is a selective α7 nAChR agonist and the aim of this study was to determine whether cytidine 5′-diphosphocholine (CDP-choline), or citicoline, a dietary source of choline, increases sensory gating and cognition in healthy volunteers stratified for gating level. In a randomized, placebo-controlled, double-blind design involving acute administration of low, moderate doses (500 mg, 1000 mg) of CDP-choline, 24 healthy volunteers were assessed for auditory gating as indexed by suppression of the P50 event-related potential (ERP) in a paired-stimulus (S1, S2 ) paradigm, and for executive function as measured by the Groton Maze Learning Task (GMLT) of the CogState Schizophrenia Battery. CDP-choline improved gating (1000 mg) and suppression of the S2 P50 response (500 mg, 1000 mg), with the effects being selective for individuals with low gating (suppression) levels. Tentative support was also shown for increased GMLT performance (500 mg) in low suppressors. These preliminary findings with CDP-choline in a healthy, schizophrenia-like surrogate sample are consistent with a α7 nAChR mechanism and support further trials with choline as a pro-cognitive strategy.